Long-Chain Acylcarnitines Decrease the Phosphorylation of the Insulin Receptor at Tyr1151 Through a PTP1B-Dependent Mechanism - Vilks, Karlis (Int J Mol Sci, 2021)
The accumulation of lipid intermediates may interfere with energy metabolism pathways and regulate cellular energy supplies. As increased levels of long-chain acylcarnitines have been linked to insulin resistance, we investigated the effects of long-chain acylcarnitines on key components of the insulin signalling pathway. We discovered that palmitoylcarnitine induces dephosphorylation of the insulin receptor (InsR) through increased activity of protein tyrosine phosphatase 1B (PTP1B). Palmitoylcarnitine suppresses protein kinase B (Akt) phosphorylation at Ser473, and this effect is not alleviated by the inhibition of PTP1B by the insulin sensitizer bis-(maltolato)-oxovanadium (IV). This result indicates that palmitoylcarnitine affects Akt activity independently of the InsR phosphorylation level. Inhibition of protein kinase C and protein phosphatase 2A does not affect the palmitoylcarnitine-mediated inhibition of Akt Ser473 phosphorylation. Additionally, palmitoylcarnitine markedly stimulates insulin release by suppressing Akt Ser473 phosphorylation in insulin-secreting RIN5F cells. In conclusion, long-chain acylcarnitines activate PTP1B and decrease InsR Tyr1151 phosphorylation and Akt Ser473 phosphorylation, thus limiting the cellular response to insulin stimulation.